2013
DOI: 10.1111/iar.12027
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous paleomagnetic record from the Miocene Kozagawa Dike of the Kumano Acidic Rocks, Kii Peninsula, Southwest Japan: cautionary note on tectonic interpretation

Abstract: We have conducted a paleomagnetic investigation of the Kozagawa Dike, which is part of the Kumano Acidic Rocks that are the product of a Middle Miocene volcanoplutonic complex cropping out on the Kii Peninsula of Southwest Japan. The granite porphyry facies of the dike yields stable remanent magnetization components. Precisely determined site-mean directions of characteristic components, as revealed by principal component analysis of stepwise alternating-field and thermal demagnetization results, form a tight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…In addition, the paleomagnetic directions of these tuffs are also identical to those for the Kumano-North and Kumano calderas (Hoshi, 2002;Hoshi et al, 2013;Hoshi, Miwa, et al, 2004).…”
Section: Miocene Ash-flow Deposits In the Inner Zonesupporting
confidence: 56%
See 1 more Smart Citation
“…In addition, the paleomagnetic directions of these tuffs are also identical to those for the Kumano-North and Kumano calderas (Hoshi, 2002;Hoshi et al, 2013;Hoshi, Miwa, et al, 2004).…”
Section: Miocene Ash-flow Deposits In the Inner Zonesupporting
confidence: 56%
“…Numerous radiometric ages (U-Pb, fission-track, and K-Ar) have suggested that the ash-flow tuffs, igneous and pyroclastic dikes, and laccolithic intrusions in these calderas were formed mostly from 14 to 15.5 Ma, and no significant age differences have been reported outside the bounds of analytical uncertainty (Iwano et al, 2007;Shinjoe et al, 2021). Paleomagnetic directions recorded in the Kumano-North and Kumano calderas are virtually identical, implying that these directions can be attributed to an extraordinary geomagnetic field during a period of polarity transition or excursion (Hoshi, 2002;Hoshi et al, 2013;Hoshi, Kamiya, et al, 2004;Hoshi, Miwa, et al, 2004).…”
Section: Middle Miocene Calderas In the Outer Zonementioning
confidence: 94%